2022
DOI: 10.1002/smll.202201167
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Functional Ultrasmall Gold Nanoparticles in 3D Gut Cell Models

Abstract: Ultrasmall gold nanoparticles (2 nm) easily penetrate the membranes of intestinal murine epithelial cells (MODE‐K) and colorectal cancer cells (CT‐26). They are also taken up by 3D spheroids (400 µm) of these cell types and primary gut organoids (500 µm). In contrast, dissolved dyes are not taken up by any of these cells or 3D structures. The distribution of fluorescent ultrasmall gold nanoparticles inside cells, spheroids, and gut organoids is examined by confocal laser scanning microscopy. Nanoparticles conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…In order to further increase the valency and at the same time facilitate cell uptake, we chose us-AuNPs as scaffolds for the multivalent presentation of TW and TMs. With their size of ∼2 nm, they are in the range of other small biomolecules and readily pass the cell membrane and even the brain–blood barrier . Functionalization of the gold surface with thiol-containing molecules is straightforward and leads to a very stable Au–S bond, enabling the loading and transport of drug-like molecules. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…In order to further increase the valency and at the same time facilitate cell uptake, we chose us-AuNPs as scaffolds for the multivalent presentation of TW and TMs. With their size of ∼2 nm, they are in the range of other small biomolecules and readily pass the cell membrane and even the brain–blood barrier . Functionalization of the gold surface with thiol-containing molecules is straightforward and leads to a very stable Au–S bond, enabling the loading and transport of drug-like molecules. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Consequently, the nanoparticles appear considerably smaller in DCS than they actually are. [ 11,20,22,44 ] Previous studies utilizing high resolution transmission electron microscopy (HRTEM) already revealed that the gold core is present as uniform particles with an average diameter of ≈ 2.0–2.2 nm. [ 23,44c ] The concentration of conjugated biomolecules was determined by UV–vis spectroscopy (Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…[ 51a,52 ] The underlying mechanisms have not been fully elucidated for ultrasmall nanoparticles, but it appears to be an active endocytic uptake rather than a passive membrane penetration. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations